(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article analyses the gig economy and platform employment as contemporary forms of labour relations. A comparative analysis of these phenomena is conducted: their common features and differences, as well as advantages and disadvantages for the participants, are highlighted. The hierarchical relationship is substantiated: platform employment is defined as a digital subtype of the gig economy.